AUTOMATION OF THE RIJNLAND STORAGE BASIN, THE NETHERLANDS - W. Schuurmans; P. E. R. M van Leeuwen; F. E. van Kruiningen (International Association of Lowland Technology, 2002)
The project “Automation of the storage Basin Rijnland” (ABR), was finalised at the beginning of the year 2000, that is three year later than originally planned. The project has resulted in an automatic control system for four drainage pumping stations (total capacity 150 m³/s) and an intake structure. The system can be operated with or without the intervention of a water manager. The original design of the system however, appeared not to function in practice. The system is currently running according to expectation, but its design has been adjusted drastically.